The Role and Function of Therapeutic Communication in the Success of Dental and Mouth Health Services at Puskesmas City of Makassar - Musiana, Musiana; Dewi Ruben, Sethiana; Merdekawati Surasno, Diah; Sari Soamole, Maya; Rino Vanchapo, Antonius; Suabey, Suningsih; Muhammad Adam, Andi (International Journal of Health Sciences, 2023)
Therapeutic communication is professional communication for nurses that is planned and carried out to help heal or restore patients. By having good therapeutic communication skills, nurses will more easily establish a trusting relationship with patients, and this will be more effective for nurses in providing professional satisfaction in nursing care. The purpose of this study was to find out the description of therapeutic communication in the success of dental and oral health services at the Bara-Baraya Health Center, Makassar. The type of research used is descriptive research to describe the role of therapeutic communication in the success of dental and oral health services at the Bara-Baraya Health Center Makassar. Of the 82 patients who came to visit the dental clinic at Bara-Baraya Public Health Center, there were 30 patients who were willing to be asked to fill out the questionnaire, namely 8 men (26.7%) and 22 women (73.3%). This research examines therapeutic communication at the orientation stage, work stage, and termination stage in service success and each stage is explained by the questions. From primary data processing, 30 respondents on average all stated that the stages of therapeutic communication had gone well. Based on the results of the research describing the role of therapeutic communication in the success of dental and oral health services carried out at the Bara-Baraya Health Center, it can be concluded that: a. The description of the role of therapeutic communication in the success of dental and oral health services is good and successful. b. The success rate of the first therapeutic communication is at the termination stage, then the working stage and then the orientation stage.